2022
DOI: 10.24127/ajpm.v11i4.6031
|View full text |Cite
|
Sign up to set email alerts
|

Moodle-Based Learning Media Development of Flex Model in Improving Mathematical Hard Skills of High School Students

Abstract: The development of the flex media model looks like the beginning of the problems in the classroom, especially in the new normal. Students experience difficulties when given math problems. Students are less able to solve these problems, especially in understanding justifying mathematical ideas and arithmetic skills, and are less interested and enthusiastic when learning. This study aimed to develop a Moodle-based flex model learning media to improve students' mathematical hard skills with three-dimensional mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The student response results were measured based on data obtained from filling out response questionnaires by 35 students, with an average percentage of student responses of 89.4 % with a very positive category, meaning students like using Al-Qur'an-based MAV media on mathematical reasoning abilities as a medium. This is in line with research developed by (Amrullah et al, 2021;Darmayanti, Baiduri, & Inganah, 2022;Sugianto et al, The student learning outcomes value obtained from a test with five questions from the MAV media Al-Qur'an based on mathematical reasoning abilities will then be analyzed according to PP's minimum completeness criteria (KKM): Singa Putih Prigen, namely 75. The results showed that all students scored above the KKM or more than equal to 75, with a percentage of 8 2.9 % in the very effective category.…”
Section: Implementation Stagesupporting
confidence: 60%
See 1 more Smart Citation
“…The student response results were measured based on data obtained from filling out response questionnaires by 35 students, with an average percentage of student responses of 89.4 % with a very positive category, meaning students like using Al-Qur'an-based MAV media on mathematical reasoning abilities as a medium. This is in line with research developed by (Amrullah et al, 2021;Darmayanti, Baiduri, & Inganah, 2022;Sugianto et al, The student learning outcomes value obtained from a test with five questions from the MAV media Al-Qur'an based on mathematical reasoning abilities will then be analyzed according to PP's minimum completeness criteria (KKM): Singa Putih Prigen, namely 75. The results showed that all students scored above the KKM or more than equal to 75, with a percentage of 8 2.9 % in the very effective category.…”
Section: Implementation Stagesupporting
confidence: 60%
“…abilities, is still rare. Most of the animated video teaching materials that can be found are usually packaged and designed using the kinemaster application (Darmayanti, Baiduri, & Inganah, 2022;R. F. Putri et al, 2021).…”
Section: |mentioning
confidence: 99%
“…Budaya di Indonesia sangat beragam, setiap daerah memiliki nilai budaya masing-masing. Nilai-nilai budaya tersebut dapat dijumpai dalam aspek kebangsaan di negara ini, salah satunya adalah permainan tradisional (Darmayanti et al, 2022;Hasanah et al, 2022;Syaifuddin et al, 2022). Permainan tradisional biasanya dimainkan secara beramai-ramai oleh anak, sehingga dengan memainkan permainan tersebut dapat terciptalah suatu kebersamaan.…”
Section: Pendahuluanunclassified
“…The use of digital technologies in teaching mathematics is the subject of modern scientific research, for example Clark-Wilson, Robutti, & Thomas (2020), Hillmayr et al (2020), Astafieva et al (2019). Researchers pay special attention to the development of an educational environment for teaching mathematics on the Moodle platform (Darmayanti, Baiduri, & Inganah, 2022). Aspects of using digital mobile technologies to support IBL are described in (Becker et al, 2020).…”
Section: Analysis Of Current Researchmentioning
confidence: 99%